Religions/globalizations : theories and cases - Hopkins, Dwight N. (e-Duke books scholarly collection., 2001)
A collection of essays demonstrating the ways diverse religious rituals, symbols, ethics and ideologies perform as primary planks in the construction of the public realm, with particular focus on peripheral nations and politicized spiritualities of resist.